Let’s Hear from Service Providers: Technology and the COVID-19 Pandemic - Gateri, Hellen; Salami, Bukola; Khalema, Emily; Dhungel, Rita (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2024)
The use of digital technology during the COVID-19 pandemic advanced service delivery from in-person to virtual. This qualitative study, conducted with 20 service providers in settlement and social service agencies supporting immigrant communities in Edmonton, Alberta, uncovered significant findings. The study revealed that technology disparities markedly affected the access and delivery of services for both service providers and users. The implications of these findings underscore the urgent and pressing need for advocacy at all levels of government to ensure that all Canadians, especially the marginalized, have equitable access to affordable internet services, technology devices, and digital literacy training.